Small-scale Variation of Testate Amoeba Assemblages: the Effect of Site Heterogeneity and Empty Shell Inclusion - Lizoňová, Zuzana; Zhai, Marie; Bojková, Jindřiška; Horsák, Michal (Microbial ecology, 2019)
Studies on testate amoeba species distribution at small scales (i.e., single peatland sites) are rare and mostly focus on bogs or mineral-poor Sphagnum fens, leaving spatial patterns within mineral-rich fens completely unexplored. In this study, two mineral-rich fen sites of contrasting groundwater chemistry and moss layer composition were selected for the analysis of testate amoeba compositional variance within a single site. At each study site, samples from 20 randomly chosen moss-dominated plots were collected with several environmental variables being measured at each sampling spot. We also distinguished between empty shells and living individuals to evaluate the effect of empty shell inclusion on recorded species distribution. At the heterogeneous-rich Sphagnum-fen, a clear composition turnover in testate amoebae between Sphagnum-dominated and brown moss-dominated samples was closely related to water pH, temperature and redox potential. We also found notable species composition variance within the homogeneous calcareous fen, yet it was not as high as for the former site and the likely drivers of community assembly remained unidentified. The exclusion of empty shells provided more accurate data on species distribution as well as their relationship with some environmental variables, particularly moisture. Small-scale variability in species composition of communities seems to be a worthwhile aspect in testate amoeba research and should be considered in future sampling strategies along with a possible empty shell bias for more precise understanding of testate amoeba ecology and paleoecology.
Keywords: Bryophyta; Česká republika; Wetlands; mikrobiota; Testate amoebae; Soil; půda; mokřady; Microbiota; Fens; Empty shells; Czech Republic; Lobosea; Peatlands; Small-scale variability